1976
DOI: 10.1029/gl003i008p00429
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Mars: The role of ionospheric conductivity in the acceleration of magnetospheric particles

Abstract: Although Mercury and Mars appear to have magnetospheres of comparable size, Mercury's magnetosphere accelerates charged particles, whereas Mars' magnetosphere apparently does not. We propose that this difference results from the fact that rapid steady‐state convection, and the associated particle acceleration, cannot occur in a Martian magnetosphere because of its connection to a highly conducting ionosphere. Mercury, which has no conducting ionosphere and probably an insufficiently conducting surface, can exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 24 publications
6
171
1
Order By: Relevance
“…Such polar cap potential saturation is due to the nonlinear nature of the magnetosphere-ionosphere (M-I) coupling [Weimer et al, 1990]. Hill et al [1976] showed a current-voltage relationship, V = V M À I/AE 0, where V, V M , I, and AE 0 are the polar cap potential drop, the solar wind dynamo voltage, Birkeland current, and the critical conductivity (about 20 mho for typical solar wind parameters near the earth). It is independent of the Birkeland current.…”
Section: Discussionmentioning
confidence: 99%
“…Such polar cap potential saturation is due to the nonlinear nature of the magnetosphere-ionosphere (M-I) coupling [Weimer et al, 1990]. Hill et al [1976] showed a current-voltage relationship, V = V M À I/AE 0, where V, V M , I, and AE 0 are the polar cap potential drop, the solar wind dynamo voltage, Birkeland current, and the critical conductivity (about 20 mho for typical solar wind parameters near the earth). It is independent of the Birkeland current.…”
Section: Discussionmentioning
confidence: 99%
“…[43] It is known that the electric potentials in the polar cap exhibit a saturation effect when the z-component of the IMF becomes increasingly negative [Hill et al, 1976;Siscoe et al, 2002]. This saturation curve has been investigated extensively through observations and theory, as reviewed by Shepherd [2007], and it may explain why the nonlinear correction is required.…”
Section: Derivation Of Dt C From Auroral Heatingmentioning
confidence: 99%
“…Hill et al (1976) suggested a' conductance value of 0.1 d o , which is not unreasonable based upon the lmar measiireniei& E this value were indeed appropriate, however, the high rate of joule heating in the regolith would severely limit the duration of the current flow as the available magnetospheric energy would be quickly dissipated. The analysis of the Mariner 10 magnetic field perturbations by Slavin et al (1997), however, suggest a longer duration FAC flow, and imply a higher conductivity closure path.…”
Section: How Will the Messnenger Observations Be Used To Discover Thementioning
confidence: 99%
“…These perturbations were first examined by Slavin et al (1997) who concluded that the spacecraft crossed three field-aligned current (FAC) sheets similar to those often observed at the Earth (Iijima and Potemra, 1978). The path by which these currents close is not known, but their existence may indicate that the conductivity of the regolith is greater than is usually assumed on the basis of analogy with the lunar surface (e.g., Hill et al, 1976). Indeed, arguments can be made for a wide range of regolith conductivities (Glassmeier, 1997;Janhunen and Kallio, 2004).…”
Section: Several Groups Have Estimated the Magnetic Moment Of Mercurymentioning
confidence: 99%